Study of Homecare Acceptance by The Elderly in The COVID-19 Era - Siregar, Nova Sontry Node; Hasibuan, Nadia; Simamora, Mayes Felda; Silaban, Lidia; Simamora, Debora (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2023)
During the COVID-19 pandemic, the care of elderly patients underwent significant changes. Society tends to avoid interaction outside the family, encouraging increased care of elderly patients at home. In this situation, the role of medical personnel becomes essential. This study examines how knowledge, culture, and interest influence homecare services during a pandemic. Respondents regarding homecare were collected from 71 families through a questionnaire. Data analysis includes univariate, bivariate and multivariate aspects to provide an overview of the relationship between variables. All data were analyzed using SPSS software. The result of this study shows p-value of each construct is less than 0.10, which indicates a strong relationship between variables. The findings show that knowledge influences family decisions about home care (p-value=0.024<0.10), while culture (pvalue=0.999>0.10) and interests (p-value=0.999>0.10) do not support acceptance of this service for the elderly. Therefore, it is hoped that respondents will increase their knowledge of improving elderly care and utilization of health services, which will positively impact the quality of life in old age. An in-depth discussion of these findings is carried out in a research paper.